If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1(6 + 4x) = 14 + 2x 2x + (6 * -1 + 4x * -1) = 14 + 2x 2x + (-6 + -4x) = 14 + 2x Reorder the terms: -6 + 2x + -4x = 14 + 2x Combine like terms: 2x + -4x = -2x -6 + -2x = 14 + 2x Solving -6 + -2x = 14 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -6 + -2x + -2x = 14 + 2x + -2x Combine like terms: -2x + -2x = -4x -6 + -4x = 14 + 2x + -2x Combine like terms: 2x + -2x = 0 -6 + -4x = 14 + 0 -6 + -4x = 14 Add '6' to each side of the equation. -6 + 6 + -4x = 14 + 6 Combine like terms: -6 + 6 = 0 0 + -4x = 14 + 6 -4x = 14 + 6 Combine like terms: 14 + 6 = 20 -4x = 20 Divide each side by '-4'. x = -5 Simplifying x = -5
| .3(b+6)=.4b+8 | | 1/3(9n+12) | | (-1)-(-16)-(-2+7)= | | (x+2)+(3x-4)=18 | | 5x+40/8 | | 3m-1=6 | | 2a-3/5a+7 | | 1/2(4x-1) | | 4y-11=5y+7 | | (3/2x+1)-(10/x-3)=1 | | 9(5x+12)+6x=4x+3 | | 5x-7=56-2x | | 6y-1=4y+1 | | 1/3(6+3)=2x-5 | | 15=4x^2-2x+4 | | v=xyz | | a^3c-3bc-a^3+3b=0 | | z/3.2+7.42 | | 10=4x^2-2x+4 | | 42-6x-13=-29 | | 5x^3=-3xy+2 | | y/0.4=-4.2 | | 100-4x=132+24 | | 5-3(7-3x)=9(x-1) | | 4/5d-1/5d=7/10 | | 7(x+1)=5x+1/2 | | x+2.7=6.0 | | .6*600+.2x=.3(600+x) | | x(x+3)2x=23 | | -139-10x=9x+15 | | -7.6-(-10.1)= | | 11x-4x=2x-7 |